A Fluorescent Probe for Detecting Mycobacterium tuberculosis and Identifying Genes Critical for Cell Entry - Yang, Dong; Ding, Feng; Mitachi, Katsuhiko; Kurosu, Michio; Lee, Richard E.; Kong, Ying (Frontiers in Microbiology, 2016)
ABSTRACT The conventional method for quantitating Mycobacterium tuberculosis (Mtb) in vitro and in vivo relies on bacterial colony forming unit (CFU) enumeration on agar plates. Due to the slow growth rate of Mtb, it takes 3-6 weeks to observe visible colonies on agar plates. Imaging technologies that are capable of quickly quantitating both active and dormant tubercle bacilli in vitro and in vivo would accelerate research towards the development of anti-TB chemotherapies and vaccines. We have developed a fluorescent probe that can directly label the Mtb cell wall components. The fluorescent probe, designated as DLF-1, has a strong affinity to the D-Ala-D-Ala unit of the late peptidoglycan intermediates in the bacterial cell wall. We demonstrate that DLF-1 is capable of detecting Mtb in both the active replicating and dormant states in vitro at 100 nM without inhibiting bacterial growth. The DLF-1 fluorescence signal correlated well with CFU of the labeled bacteria (R2=1 and 0.99 for active replicating and dormant Mtb, respectively). DLF-1 can also quantitate labeled Mtb inside of cells. The utility of DLF-1 probe to quantitate Mtb was also successfully applied to identify genes critical for cell invasion. In conclusion, this novel near infrared imaging probe provides a powerful new tool for enumerating Mtb with potential future use in bacterial virulence study.